(untitled) (Texas Journal of Medical Science, 2024)
The work is based on the results of examination and treatment of 444 children with congenital obstructive diseases of the urinary tract. Based on their results, differentiated treatment was prescribed. Children with functionally conditioned hydronephrosis and bladder-dependent variant of urodynamic disorder in obstructive megaureter received conservative treatment. In case of ureteral variant of functional form of obstructive megaureter and vesicoureteral reflux (VUR) of II–III degree, minimally invasive endoscopic treatment methods were used.